2013
DOI: 10.3109/13625187.2013.777829
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, religious affiliation, and patterns of sexual activity and contraceptive use in France

Abstract: Objective To examine the association between religiosity and sexual and contraceptive behaviours in France. Methods Data were drawn from the 2005 Health Barometer survey, a random sample of 7,495 women and 5,634 men aged 15 to 44. We used logistic regression models to study the associations between religiosity and sexual and contraceptive behaviours, by gender and religious denomination. Results Three quarters of respondents (73%) reported no religious practice, 20% practised occasionally, and 7% regularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 21 publications
2
19
1
3
Order By: Relevance
“…These country variations seem similar to those in population survey-based observations among never married 15-19 year old women and 15-24 year old men, where modern contraceptive non-use in Nigeria was among women 69% and men 58%, in India (women 82% and men 82%), in the Philippines 96% among women, and in Colombia 41% among women. 2 The study found, in agreement with other studies 10,14,15,17,18 , that younger age, a higher degree of religiosity or intrinsic religiosity and religious affiliation (Hindu and Muslim) were associated with contraception non-use. According to WHO 13 , reasons for a global unmet need for contraception particularly include young people and cultural or religious opposition.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These country variations seem similar to those in population survey-based observations among never married 15-19 year old women and 15-24 year old men, where modern contraceptive non-use in Nigeria was among women 69% and men 58%, in India (women 82% and men 82%), in the Philippines 96% among women, and in Colombia 41% among women. 2 The study found, in agreement with other studies 10,14,15,17,18 , that younger age, a higher degree of religiosity or intrinsic religiosity and religious affiliation (Hindu and Muslim) were associated with contraception non-use. According to WHO 13 , reasons for a global unmet need for contraception particularly include young people and cultural or religious opposition.…”
Section: Discussionsupporting
confidence: 82%
“…13 Among university students factors associated with contraceptive non-use for women, men or both can be summarized as follows: 1) socio-demographic factors (younger age, lower educational level 10,14,15 , being male 16 , higher degree of religiosity 17,18 , high price of contraceptives 14 ); 2) Sexual behaviour (early sexual debut 10,16,19 , not previously pregnant 20 , more than one sexual partner in the past 12 months 20 , internet use (sex) 21,22 ; Psychosocial factors or internal assets (low locus of control, low personal initiative and assertiveness 14 , lack of life satisfaction 23 , and psychological distress 24,25 ), and 3) other factors (fear of side effects of modern contraceptives 7 , lack of exposure to healthcare worker talking about contraception 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less engagement in risky sexual behaviors among religious people compared with non-religious people may also explain the important implications of religiosity in coping with sexual dysfunctions. 31,32 Anxiety and depressive mood Apart from religious coping, we were also able to observe a significant association between anxiety and depressive mood and erectile function in men with SCI. It has been repeatedly shown that depressive mood and anxiety levels are high in patients with SCI.…”
Section: Religious Copingmentioning
confidence: 57%
“…The proportion of private government-dependent schools that are religious schools is~60 %, 20 and religiousness has been associated with lower contraceptive use. 42 It is also possible that risky sexual behaviors are increasing among students with lower socioeconomic status because the nature of the source database did not allow us to distinguish between students attending private government-dependent schools and those attending private schools, which likely come from the most socioeconomically advantaged families. 21 Several studies have explored differences in sexual behavior between types of school and have found that pupils in public schools are less aware of contraceptive methods and are more likely to undertake risky sexual activities, 22,43 although these results are not consistent with ours.…”
Section: Trends In Condom Usementioning
confidence: 99%